Dementia : the basics - Innes, Anthea (Basics (Taylor & Francis), 2021)
"This book provides the reader with an overview of the basics in relation to dementia, dealing with different areas of the dementia journey: pre-diagnosis, diagnosis, post-diagnostic support, increasing care needs and support, and end of life care. Written by people from different backgrounds and disciplines, the book endeavours to raise awareness of dementia; challenge stereotypical and negative ideas about what it means to have dementia; and champion a society where people living with dementia can be active as they wish for as long as possible. Providing an overview of the evidence and knowledge from research and lived experiences, this book enhances understanding of dementia, and perhaps challenges thinking about what it might be like to live with a diagnosis or provide care to a loved one. Dementia is something that deserves policy, practice, research and society's attention, and the book asks to consider what any initiative or action might mean for the person living with dementia and their families and care supporters. Offering ideas and tips that can be adapted and implemented, this book is ideal for health and social care professionals, a student of social care or healthcare, a person with dementia, a carer, or someone who has an interest in the subject"--